Essential oils from Dysphania genus: Traditional uses, chemical composition, toxicology, and health benefits - Dagni, Amal; Hegheș, Simona Codruta; Suharoschi, Ramona; Pop, Oana Lelia; Fodor, Adriana; Vulturar, Romana; Cozma, Angela; Aniq filali, Oufaa; Vodnar, Dan Cristian; Soukri, Abdelaziz; El Khalfi, Bouchra (Frontiers in Pharmacology, 2022)
The genus Dysphania belongs to the Amaranthaceae family, and is known for its many health benefits. Therefore, it is commonly available worldwide and includes more than 47 species, five species have been mainly reported, and D. ambrosioides has been one of the most widely used plants for thousands of years as a remedy for a variety of ailments. In recent investigations, the essential oils of the genus Dysphania have been examined for there antibacterial, antioxidant, and antiviral properties related to specific components such as terpenoid compounds that exhibit pharmacological activity. Moreover, some of Dysphania’s compounds show a toxicological effect. Therefore, the objective of the study was to provide EO phytochemical composition and pharmacological data of the genus Dysphania.